EFL STUDENTS’ RESPONSES ON ONLINE LEARNING PROCESS DURING COVID-19 SITUATION IN INDONESIA - Syayid Sandi Sukandi (Universitas Bung Hatta, 2022)
Indonesian EFL students faced online teaching and learning in such a rapid process. Therefore, this research was carried out to search for EFL students in Indonesia about their responses on teaching and learning online. This research applied the action research method with the paradigm of quantitative descriptive approach. Data for this research was collected via an online questionnaire, distributed to one class size sample consisting of 32 students in the even semester of the 2019/2020 academic year at one of the private colleges in the West Sumatra province of Indonesia. The data were analysed by descriptive statistics, especially the percentage of each item available in the questionnaire. Findings of this research show that the respondents, or the students, had their evaluation toward the online teaching and learning. The significance of this research is that their responses briefly invite us as scholars, teachers, and lecturers, or scholar-practitioners, to think about the feasibility condition of online teaching and learning, that it should be done contextually and prepared carefully. The Covid-19 pandemic situation has forced students to face double challenges in education: learning the materials in such a digitalized situation and handling external issues emerging while learning online. REFERENCES Adara, R. A., & Puspahaty, N. (2021). How EFL Learners Maintain Motivational Factors and Positive Attitudes during COVID-19 Pandemic: A Qualitative Study. ENGLISH FRANCA?: Academic Journal of English Language and Education, 5(2), 277–298. https://doi.org/10.29240/EF.V5I2.3398 Adedoyin, O. B., & Soykan, E. (2020). Covid-19 pandemic and online learning: the challenges and opportunities. Interactive Learning Environments, 30(1), 1–13. https://doi.org/10.1080/10494820.2020.1813180 Adnan, M. (2020). Online learning amid the COVID-19 pandemic: Students perspectives. Journal of Pedagogical Sociology and Psychology, 1(2), 45–51. https://doi.org/10.33902/jpsp.2020261309 Al-Haji, B., & Al-Senafi, B. (2021, September 27). Teaching English Writing Remotely During COVID-19 in College of Basic Education Kuwait. International Journal of English Language Teaching. https://ssrn.com/abstract=3931183 Ali Ta‘amneh, M. A. A. (2021). Attitudes and challenges towards virtual classes in learning English language courses from students‘ perspectives at taibah university during covid-19 pandemic. Journal of Language Teaching and Research, 12(3), 419–428. https://doi.org/10.17507/jltr.1203.12 Ali, W. (2020). Online and Remote Learning in Higher Education Institutes: A Necessity in light of COVID-19 Pandemic. Higher Education Studies, 10(3), 16. https://doi.org/10.5539/hes.v10n3p16 Amate, J. J. S., de la Rosa, A. L., Cáceres, R. G., & Serrano, A. V. (2021). The effects of covid-19 in the learning process of primary school students: A systematic review. In Education Sciences (Vol. 11, Issue 10). https://doi.org/10.3390/educsci11100654 Andhini, A., & Hamzah. (2021). Students‘ Perception on Online Learning Media for Learning English Writing Skill during Covid-19 Pandemic. Proceedings of the Eighth International Conference on English Language and Teaching (ICOELT-8 2020), 579, 202–206. https://doi.org/10.2991/assehr.k.210914.039 Andres, L. (2017). Designing & Doing Survey Research. In Designing & Doing Survey Research. SAGE. https://doi.org/10.4135/9781526402202 Avni, S., & Lynn-Sachs, M. (2021). Change and Challenge: Jewish Education in the Time of COVID-19. In Journal of Jewish Education. https://doi.org/10.1080/15244113.2021.1995242 Betaubun, M. (2021). The Students‘ Attitude and Learning Experience toward Flipped Classroom Implementation During COVID-19 Outbreak: A Survey Study. Jurnal Pendidikan Progresif, 11(1), 54–62. https://doi.org/10.23960/JPP.V11.I1.202105 Bhandari, B., Chopra, D., Mavai, M., Verma, R., & Gupta, R. (2021). Online teaching and learning during COVID era: Medical students‘ feedback and their perspectives. Research Square, 1–11. https://doi.org/10.21203/rs.3.rs-595739/v1 Blair, J., Czaja, R. F., & Blair, E. A. (2014). Designing Surveys: A Guide to Decisions and Procedures. SAGE Publications, Inc. Blaxter, L., Hughes, C., & Tight, M. (2006). How to Research (3rd ed.). Open University Press. Bridwell-Bowles, L. (1991). Research in Composition: Issues and Methods. In E. Lindemann& G. Tate (Eds.), An Introduction to Composition Studies (pp. 94–112). Oxford University Press. Carrillo, C., & Flores, M. A. (2020). COVID-19 and teacher education: a literature review of online teaching and learning practices. European Journal of Teacher Education, 43(4), 466–487. https://doi.org/10.1080/02619768.2020.1821184 Choudhury, R. U. (2014). The Role of Culture in Teaching and Learning of English As a ForeignLanguage. Express, an International Journal of Multi Disciplinary Research, 1(4), 2348–2052. Diana, N., Yunita, W., &Harahap, A. (2021). Student‘ Perception and Problems in Learning English Using Google Classroom During the Covid-19 Pandemic. Linguists?: Journal Of Linguistics and Language Teaching, 7(1), 10. https://doi.org/10.29300/ling.v7i1.4274 Flores, M. A., Barros, A., Simão, A. M. V., Pereira, D., Flores, P., Fernandes, E., Costa, L., & Ferreira, P. (2021). Portuguese higher education students‘ adaptation to online teaching and learning in times of the COVID-19 pandemic: personal and contextual factors. Higher Education. https://doi.org/10.1007/s10734-021-00748-x Fowler, F. J. (2014). Survey Research Methods (5th ed.). SAGE Publications, Inc. Francis, K., Salter, J., Costanzo, L., Desmarais, S., Troop, M., &Parahoo, R. (2019). Scribe hero: An online teaching and learning approach for the development of writing skills in the undergraduate classroom. Online Learning Journal, 23(2), 217–234. https://doi.org/10.24059/olj.v23i2.1531 Fry, H., Ketteridge, S., & Marshall, S. (2003). A Handbook for Teaching and Learning in Higher Education: Enhancing Academic Practice (3rd ed.). Routledge, Taylor & Francis Group. Goldenberg, C., Reese, L., &Rezaei, A. (2011). Contexts for Language and Literacy Development among Dual-Language Learners. In A. Y. Dorgunoglu& C. Goldenberg (Eds.), Language and Literacy Development in Bilingual Settings. The Guilford Press. Hall, T., Byrne, D., Bryan, A., Kitching, K., Chróinín, D. N., O‘Toole, C., &Addley, J. (2021). COVID-19 and education: positioning the pandemic; facing the future. In Irish Educational Studies (Vol. 40, Issue 2, pp. 147–149). https://doi.org/10.1080/03323315.2021.1915636 Hamsia, W., Riyanto, Y., &Arianto, F. (2021). Online Learning for English Language Learners During Covid-19 Pandemic in Muhammadiyah University of Surabaya. Journal of Education and Practice, 12(9). https://doi.org/10.7176/jep/12-9-10 Haron, H., Al-abri, A., &Alotaibi, N. M. (2021). The Use of WhatsApp in Teaching and Learning English During COVID Students Perception and. International Journal of Innovation, Creativity and Change. Www.Ijicc.Net, 15(3), 1014–1033. https://orcid.org/0000-0001-6346-5321, Heilker, P. (1996). Composing/Writing. In P. Heilker& P. Vandenberg (Eds.), Keywords in Composition Studies (pp. 40–45). Boynton/Cook Publishers HEINEMANN. Hermanto, Y. B., & Srimulyani, V. A. (2021). The Challenges of Online Learning During the Covid-19 Pandemic. JurnalPendidikan Dan Pengajaran, 54(1), 46. https://doi.org/10.23887/jpp.v54i1.29703 Hofer, S. I., Nistor, N., &Scheibenzuber, C. (2021). Online teaching and learning in higher education: Lessons learned in crisis situations. Computers in Human Behavior, 121. https://doi.org/10.1016/j.chb.2021.106789 Hoofman, J., & Secord, E. (2021). The Effect of COVID-19 on Education. In Pediatric Clinics of North America (Vol. 68, Issue 5, pp. 1071–1079). https://doi.org/10.1016/j.pcl.2021.05.009 Jin, G., He, L., & Tsai, S. B. (2021). An Empirical Study on Virtual English Teaching System Based on the Microservice Architecture with Wireless Internet Sensor Network. Mathematical Problems in Engineering, 2021. https://doi.org/10.1155/2021/8494410 Johnson, D. M. (1992). Approaches to Research in Second Language Learning. Longman. Kamal, M. I., Zubanova, S., Isaeva, A., &Movchun, V. (2021). Distance learning impact on the Engl ish language teaching during COVID-19. Education and Information Technologies, 26(6), 7307–7319. https://doi.org/10.1007/s10639-021-10588-y Khan, R. A., Atta, K., Sajjad, M., &Jawaid, M. (2021). Twelve tips to enhance student engagement in synchronous online teaching and learning. Medical Teacher. https://doi.org/10.1080/0142159X.2021.1912310 Khrismaninda, E. R., & Refnaldi, R. (2021). An Analysis of Students‘ Perception and Motivation In Learning English By Using Google Classroom During Covid-19 Pandemic In The Eleventh Graders At Sma N 1 Kec. Payakumbuh. Journal of English Language Teaching, 10(4), 588–598. https://doi.org/10.24036/JELT.V10I4.114911 Li, J. (2021). Design, Implementation, and Evaluation of Online English Learning Platforms. Wireless Communications and Mobile Computing, 2021. https://doi.org/10.1155/2021/5549782 Liu, H., & Song, X. (2021). Exploring ?Flow? in young Chinese EFL learners‘ online English learning activities. System, 96. https://doi.org/10.1016/j.system.2020.102425 Lodico, M. G., Spaulding, D. T., &Voegtle, K. H. (2010). Methods in Educational Research: FromTheory to Practice. Jossey-Bass, A Wiley Imprint. Lynch, M. M. (2004). Learning Online: A Guide to Success in the Virtual Classroom. Routledge Falmer. Manen, M. Van. (1999). The Language of Pedagogy and the Primacy of Student Experience. In J. Loughran (Ed.), Researching Teaching: Methodologies and Practices for Understanding Pedagogy (pp. 19–22). Falmer Press. Martin, F., Bacak, J., Polly, D., &Dymes, L. (2021). A systematic review of research on K12 online teaching and learning: Comparison of research from two decades 2000 to 2019. In Journal of Research on Technology in Education. https://doi.org/10.1080/15391523.2021.1940396 McAvinia, C. (2016). Online Learning and its Users: Lessons for Higher Education. Chandos Publishing. Moorhouse, B. L., & Kohnke, L. (2021). Responses of the English-Language-Teaching Community to the COVID-19 Pandemic. In RELC Journal (Vol. 52, Issue 3, pp. 359–378). SAGE Publications Sage UK: London, England. https://doi.org/10.1177/00336882211053052 Mu‘awanah, N., Sumardi, S., &Suparno, S. (2021). Using Zoom to Support English Learning during Covid-19 Pandemic: Strengths and Challenges. JurnalIlmiahSekolahDasar, 5(2), 222. https://doi.org/10.23887/jisd.v5i2.35006 Nardi, M. P. (2014). Doing Survey Research: A Guide to Quantitative Methods (3rd ed.). Routledge. Nazir, M. (2014). MetodePenelitian. PenerbitGhalia Indonesia. Ng, P. T. (2021). Timely change and timeless constants: COVID-19 and educational change in Singapore. Educational Research for Policy and Practice, 20(1), 19–27. https://doi.org/10.1007/s10671-020- 09285-3 Norton, L. (2003). Assessing Student Learning. In A Handbook for Teaching and Learning in Higher Education: Enhancing Academic Practice (3rd ed., p. 137). Routledge. Norton, L. S. (2009). Action Research in Teaching and Learning: A Pedagogical Guide to Conducting Pedagogical Research in Universities. Routledge. Octaberlina, L. R., & Muslimin, A. I. (2020). EFL students perspective towards online learning barriers and alternatives using Moodle/Google classroom during Covid-19 pandemic. International Journal of Higher Education, 9(6), 1–9. https://doi.org/10.5430/ijhe.v9n6p1 Osman, M. E. T. (2020). Global impact of COVID-19 on education systems: the emergency remote teaching at Sultan Qaboos University. Journal of Education for Teaching, 46(4), 463–471. https://doi.org/10.1080/02607476.2020.1802583 Pasaribu, T. A., & Dewi, N. (2021). Indonesian EFL students‘ voices on online learning during COVID-19 through appraisal analysis. LEARN Journal: Language Education and Acquisition Research Network, 14(1), 399–426. https://so04.tci-thaijo.org/index.php/LEARN/index Purnama, Y. (2021). Teacher‘s Obstacles in English Online Learning during Covid-19 Pandemic. Metathesis: Journal of English Language, Literature, and Teaching, 5(2), 228–239. https://doi.org/10.31002/METATHESIS.V5I2.3618 Rea, L. M., & Parker, R. A. (2012). Designing & Conducting Survey Research: A Comprehensive Guide (3rd ed.). Jossey-Bass, A Wiley Imprint. Rothan, H. A., & Byrareddy, S. N. (2020). The epidemiology and pathogenesis of coronavirus disease (COVID-19) outbreak. In Journal of Autoimmunity (Vol. 109). Academic Press. https://doi.org/10.1016/j.jaut.2020.102433 Sadeghpour, M., & Sharifian, F. (2019). World Englishes in English language teaching. World Englishes, 38(1–2), 245–258. https://doi.org/10.1111/weng.12372 Shi, J., & Fan, L. (2021). Investigating Teachers‘ and Students‘ Perceptions of Online English Learning in a Maritime Context in China. SAGE Open, 11(3). https://doi.org/10.1177/21582440211040800 Subekti, A. S. (2021). Covid-19-Triggered Online Learning Implementation: Pre-Service English Teachers‘ Beliefs. Metathesis: Journal of English Language, Literature, and Teaching, 4(3), 232. https://doi.org/10.31002/metathesis.v4i3.2591 Sudarsana, I. K., Armaeni, K. W. A., Sudrajat, D., Abdullah, D., Satria, E., Saddhono, K., Samsiarni, Setyawasih, R., Meldra, D., &Ekalestari, S. (2019). The Implementation of the E-Learning Concept in Education. Journal of Physics: Conference Series, 1363(1). https://doi.org/10.1088/1742-6596/1363/1/012063 Sugiyono. (2016). MetodePenelitianKualitatif, Kuantatifdan R & D. PT. Alfabet. Suryani, D., Yunita, W., &Harahap, A. (2021). EFL Teacher ‘s Reasons , Problems and Solution of Using Google Classroom in Teaching Learning English During Covid-19 Pandemic in Bengkulu. Journal of English Education and Linguistics, 4(2), 1–19. https://doi.org/10.32663/EDU-LING.V4I2.1982 Teng, M. F., Wang, C., & Wu, J. G. (2021). Metacognitive Strategies, Language Learning Motivation, Self-Efficacy Belief, and English Achievement During Remote Learning: A Structural Equation Modelling Approach. RELC Journal. https://doi.org/10.1177/00336882211040268 Thaheem, S. K., ZainolAbidin, M. J., Mirza, Q., &Pathan, H. U. (2021). Online teaching benefits and challenges during pandemic COVID-19: a comparative study of Pakistan and Indonesia. Asian Education and Development Studies. https://doi.org/10.1108/AEDS-08-2020-0189 Vivolo, J. (Ed.). (2020). Managing Online Learning: The Life-Cycle of Successful Programs. Routledge. Walidaini, F. A. (2021). The Use of WhatsApp Application for Learning English Online during Corona Virus Disease-19 Pandemic. RETAIN (Research on English Language Teaching in Indonesia, 9(1), 167–173. https://ejournal.unesa.ac.id/index.php/retain/article/view/39661 Wicaksono, A. P. (2021, November 6). Tantangan Pembelajaran Bahasa Inggris Dibahas, Dua Kampus Kolaborasi-Suara Merdeka. Suara Merdeka. https://www.suaramerdeka.com/pendidikan/pr-041609815/tantangan-pembelajaran-bahasa-inggris- dibahas-dua-kampus-kolaborasi Wolff, D. (2002). Asynchronous Online Teaching. In D. Roen, V. Pantoja, L. Yena, S. K. Miller, & E. Waggoner (Eds.), Strategies for Teaching First-Year Composition. National Council of Teachers of English. Xu, J. (2021). Chinese University Students‘ L2 Writing Feedback Orientation and Self-Regulated Learning Writing Strategies in Online Teaching During COVID-19. Asia-Pacific Education Researcher, 30(6), 563–574. https://doi.org/10.1007/S40299-021-00586-6/TABLES/4 Yan, L., Whitelock-Wainwright, A., Guan, Q., Wen, G., Gaševi?, D., & Chen, G. (2021). Students‘ experience of online learning during the COVID-19 pandemic: a province-wide survey study. British Journal of Educational Technology, 52(5), 2038–2057. https://doi.org/10.1111/BJET.13102